The relationship between milk urea nitrogen content and urinary nitrogen excretion as determined in 4 Swiss dairy breeds - A. Burren; M. Terranova; M. Kreuzer; T. Kupper; S. Probst (Journal of Dairy Science)
ABSTRACT: Ammonia (NH3) originating from agriculture substantially contributes to the environmental nitrogen load and threatens sensitive ecosystems by inducing eutrophication and acidification of the soil. To strategically minimize NH3 emissions, this study aimed to develop a model to predict urinary nitrogen (UN) excretion (g/d), the major NH3 source of cows of different dairy breeds, based on an easy-to-determine proxy as an on-farm tool. For that purpose, dietary characteristics were not considered. One such proxy would be the MUN content, which could be determined in tank milk samples from dairy farms. We therefore investigated the UN and MUN values from 21 different feeding experiments performed in Switzerland with 4 contrasting dairy breeds. These were 162 Brown Swiss (BS), 348 Holstein (HO), 44 Jersey (JE), and 50 Swiss Fleckvieh (SF) cows. We investigated the relationship between the coefficients of the UN and MUN using various linear mixed models. The forward model selection demonstrated that it is essential to consider the interaction between MUN and breed, as well as BW and breed, when modeling UN. Furthermore, there was a pronounced heteroscedasticity between UN and MUN for higher MUN values (>14 mg/dL). This heteroscedasticity must be accounted for, either through explicit modeling or log transformation. The final model included fixed effects, MUN, BW, and breed, the interactions, MUN × breed and BW × breed, as well as the experiment as random effect. This model also considered the heteroscedasticity. In the final model, R2 was high, at 81.2%. The regression coefficients and highest posterior density intervals were 7.28 (5.42; 9.02), 10.41 (9.16; 11.65), 9.00 (6.20; 11.94) and 11.79 (9.15; 14.25) g/d of increase in UN per mg/dL of MUN for BS, HO, JE, and SF, respectively. The estimated regression coefficients for BW and highest posterior density intervals were 0.09 (−0.01; 0.19), 0.17 (0.11; 0.27), 0.51 (0.21; 0.80) and 0.28 (0.03; 0.53) for BS, HO, JE, and SF, respectively. The estimated marginal means ± SE for UN (g/d) were 117 ± 12, 147 ± 12, 119 ± 14, and 135 ± 14 for BS, HO, JE, and SF, respectively. These results confirm MUN content to be a useful tool to predict UN excretion in lactating dairy cows, as suggested by previous studies. However, in contrast to previous findings, our results underscore the necessity of accounting for breed and BW in the predictive model. The established model improves the accuracy of mass flow models that estimate NH3 emissions based on the UN excretion of livestock at the beginning of the manure management chain.